ANCAMAN PERIKANAN SKALA KECIL TERHADAP HIU DI SUMENEP UNTUK KEBUTUHAN PENGELOLAAN YANG EFEKTIF DAN BERKELANJUTAN - Doni Ferdiansyah; M.Taufiq Hidayat (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2016)
ABSTRACT The high demand of shark products, particularly fins, have influenced the increase in the exploitation and trade of sharks, included small scale fisheries. The condition can increase the vulnerability of sharks because of their biological cycle and as a top predator and economically important fish. This paper aims to identify the conditions of exploitation and management of sharks in Sumenep Regency. The method used in this research is the field observation, in-depth interview and review of policies. Based on the existing results indicate that over-exploitation has occurred in Sumenep, where fishermen catch almost any size shark, both great until the baby sharks ('baby hiu’) in large numbers. Several species of sharks that many caught are the species Carcharhinus melanopterus, C. obscurus, Sphyrna lewini and Chiloscyllium punctatum. Shark trade activities occur in Tempat Pelelangan Ikan (TPI) of Pasongsongan, the fishing port of Ambunten, Dasuk, Dungkek, and Tanjung–Saronggi. Currently, the regulations governing the management and protection of sharks in Indonesia is still limited to only a few species of sharks, including whale sharks (Rhincodon typus), shark saws (Pristis Microdon, P. clavata, P. zijsron, and Anoxypritis cuspidata), and manta rays (Manta birostris and M. Alfredi), although other species has status Near Threatened until Endengered based International Union for Conservation of Nature (IUCN) and Appendix II based on the Convention on International Trade in Endangered species (CITES). Not to socialized existing regulations to the fishermen, the absence of regional policy in particular, and the high price is one reason still rampant shark fishing on a large scale. To that end, public awareness activities to fishermen and communities and appropriate regulation is needed in sustainable shark management efforts